Les sites industriels dans l’agglomération québécoise - Trotier, Louis (Cahiers de géographie du Québec, 1961)
Even though manufacturing establishments are dispersed throughout the Québec metropolitan area, many of them are concentrated in what may be called industrial zones. The principal characteristics of these various zones are examined in this paper, with particular emphasis on the location factors. Four of these factors appear to have been responsible for the selection of most of the various industrial sites: 1. The transport facilities ; 2. Cheap land ; 3. The possibility of extension ; 4. The proximity of labour.